Optimizing the Role of Information and Communication Technology in Educational Transformation - Sudi, Mohamad; Irwan, Irwan; Oci, Markus; Arroyan, Muhammad; Purwosusanto, Hery (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Educational transformation is a form of effort to make changes in the world of education. Many things can be used as a tool to help realize change or innovation in the world of education. Along with the times, technology has played a significant role in making changes to the world of education. The role of technology cannot be denied, because with the existence of technology the education system begins to develop. The involvement of this technology is a source of change in the learning process, both with the support of information and communication technology. This information and communication technology needs to be used optimally and properly so that its role reaches all students. The purpose of this research is to find out that by optimizing the Role of Information and Communication Technology in Educational Transformation, education that is novel in nature will be realized both from the media used and the teaching methods used by educators. In addition, through information and communication technology, it is also hoped that it can provide innovations and solutions to current problems in the world of education and also as an opening for the transformation of education in Indonesia. The method used in this study is a quantitative method. The researcher conducted a survey by providing a questionnaire link using a Google form which contained several statements to be filled in by students. The results obtained by the researcher were the students' very positive responses to this research and the enthusiasm of the students in filling out the questionnaire link that the researchers provided. The results of the study also show that the role of information and communication technology in educational transformation is quite optimal, but educators need the latest breakthroughs to further optimize their use. The conclusion from this study is that the role of information and communication technology in educational transformation is already optimal but needs serious attention so that information and communication technology can be more optimal in its use in the educational process. The limitations of this study are that researchers only conduct research on schools and researchers do not directly conduct research at schools but by distributing questionnaire links on a Google form containing statements related to optimizing the role of information and communication technology in educational transformation.